Assessment of Climate Change Mitigation Policy Elements in Oye-Ekiti, Ekiti State, Nigeria - Adejumo, Aderinola A.; Otugboyega, Joseph Olusoji; Obajaja, Caleb Ofumi; Madu, Francis Ugochukwu; Ayo, Itunu Oluwatosin; Aregbesola, Foluso Bolanle; Agbeto, Oluwaseyifunmi B.; Salami, Kaseem Dele (Journal of Science Research and Reviews, 2025)
The implementation of effective Climate Change Mitigation Policies (CCMPs) is vital for protecting local communities from the adverse effects of climate variability. However, in rural settings like Oye-Ekiti, Nigeria, the enforcement of CCMPs is often lacking, and institutional coordination is inadequate to meet national climate objectives. This study assessed the Climate Change Mitigation Policy Elements (CCMPE) in Oye-Ekiti, identifying existing policies, awareness levels, and challenges to implementation. A simple random sampling method selected 120 stakeholders in environmental use, including farmers, artisans, traders, and forestry staff. Data were collected through secondary sources and a structured questionnaire, analyzing existing CCMPE, awareness of climate change, effectiveness in reducing greenhouse gas emissions, stakeholder participation, and enforcement levels. The findings indicate that respondents were aware of climate change (68.3%) but lacked understanding of greenhouse gases (71.7%). About 32.5% were unsure of CCMPE effectiveness in reducing emissions. Many were unaware of government programs (53.3%) and enforcement agents (56.7%), with only 43.3% occasionally involved in policy implementation. Identified CCMPE included tree planting and efficient waste management. Educational status, communication methods, government program awareness, and presence of enforcement agents significantly influenced stakeholders’ participation. The study concludes that CCMPs are not yielding desired results due to low awareness and lack of strict measures for effective implementation. The government must address these gaps to achieve desired results, including increasing awareness, improving enforcement, and ensuring stakeholder participation.